Kant on Race and Barbarism: Towards a More Complex View on Racism and Anti-Colonialism in Kant. Issue 3 (September 2019) - Eberl, Oliver
Abstract: Whether Kant's late legal theory and his theory of race are contradictory in their account of colonialism has been a much-debated question that is also of highest importance for the evaluation of the Enlightenment's contribution to Europe's colonial expansion and the dispossession and enslavement of native and black peoples. This article discusses the problem by introducing the discourse on barbarism. This neglected discourse is the original and traditional European colonial vocabulary and served the justification of colonialism from ancient Greece throughout the Renaissance to the eighteenth century. Kant's explicit rejection of this discourse and its prejudices reveals his early critical stance toward colonial judgements of native peoples even before he developed his legal theory. This development of his critical position can be traced in his writings on race: although he makes racist statements in these texts, his theory of race is not meant to ground moral judgements on 'races' or a racial hierarchy but to defend the unity of mankind under the given empirical reality of colonial hierarchies.